2020
DOI: 10.31201/ijhmt.694384
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and Complementary Medicine From Health Tourism Perspective

Abstract: Health tourism, which is defined as travels for treatment, staying fit, protecting and improving health, has become an important source of income for countries in the last 20 years. Depending on globalization and the development of technology, the number of tourists traveling for health purposes is increasing rapidly in the world. In parallel with these increases, the demand for traditional and complementary medicine applications and products in the world is increasing. In Europe, more than 100 million people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Medical tourism is on the rapid rise in several developing countries such as India, Malaysia, Thailand, Turkey, and Singapore. Medical tourism is defined as 'the act of travelling abroad to obtain medical care' or 'travels for treatment' [1]. The higher cost of treatment in developed countries and the availability of competent practitioners and physicians in Asia are few factors to name for this rapid growth [2].…”
Section: Introductionmentioning
confidence: 99%
“…Medical tourism is on the rapid rise in several developing countries such as India, Malaysia, Thailand, Turkey, and Singapore. Medical tourism is defined as 'the act of travelling abroad to obtain medical care' or 'travels for treatment' [1]. The higher cost of treatment in developed countries and the availability of competent practitioners and physicians in Asia are few factors to name for this rapid growth [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, wellness experiences must be analyzed from the viewpoint of tourists or consumers to provide insights into tourist satisfaction, motivation, trustworthiness, and culture (Dryglas & Smith, 2023;Kelly, 2012;Medina-Muñoz & Medina-Muñoz, 2013). Additionally, the analysis in the current study showed that the factor "culture" was less prominent; foreign experience and interaction with others in health tourism can be significant motivators and driving factors for THT (Huang & Xu, 2018;Kelly, 2012;Kim et al, 2011;Tosun et al, 2020). Therefore, cross-cultural analysis of motivation can be incorporated into THT studies that consider factors such as ethnicity, gender and interest (Kelly, 2012).…”
Section: Emerging Gaps Recommendations and Research Framework For Fut...mentioning
confidence: 69%
“…Experience of humans in combating diseases utilising natural resources have led to the development of traditional and complementary medicine (TCM) in all cultures. [1][2][3][4][5][6][7][8] The World Health Organization (WHO) has published a report on TCM practices, practitioners and methods to prevent endangering the health of patients due to TCM. This WHO report provided information on modalities of TCM and characteristics of TCM practioners and products.…”
Section: Anah Tar Ke LI Me Ler: Geleneksel Ve Tamamlayıcı Tıp; Memnun...mentioning
confidence: 99%